2005
DOI: 10.1366/0003702054280612
|View full text |Cite
|
Sign up to set email alerts
|

Standoff Detection of High Explosive Materials at 50 Meters in Ambient Light Conditions Using a Small Raman Instrument

Abstract: We have designed and demonstrated a standoff Raman system for detecting high explosive materials at distances up to 50 meters in ambient light conditions. In the system, light is collected using an 8-in. Schmidt-Cassegrain telescope fiber-coupled to an f/1.8 spectrograph with a gated intensified charge-coupled device (ICCD) detector. A frequency-doubled Nd : YAG (532 nm) pulsed (10 Hz) laser is used as the excitation source for measuring remote spectra of samples containing up to 8% explosive materials. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
152
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(153 citation statements)
references
References 39 publications
0
152
0
Order By: Relevance
“…6 These systems focus on detecting the actual explosive device by visual characteristics such as the shape of the explosive material or detonator. 7 Other bulk detection techniques rely on the chemical structure of the explosive, such as molecular bending or twisting in terahertz (THz) spectroscopy and Raman spectroscopy, 7,8,9 and the molecular electric field gradients in nuclear quadrupole resonance (NQR).…”
Section: Bulk Explosives Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 These systems focus on detecting the actual explosive device by visual characteristics such as the shape of the explosive material or detonator. 7 Other bulk detection techniques rely on the chemical structure of the explosive, such as molecular bending or twisting in terahertz (THz) spectroscopy and Raman spectroscopy, 7,8,9 and the molecular electric field gradients in nuclear quadrupole resonance (NQR).…”
Section: Bulk Explosives Detection Methodsmentioning
confidence: 99%
“…8 Raman spectroscopy has even been applied to the standoff detection of high explosives in a silica matrix from up to 50 m away. 9 NQR detection has also been modified for standoff detection by adapting the receiving and transmitting coils and using a narrow bandwidth for detection. 11 The main disadvantage of bulk detection systems is the significant amount of explosive necessary to trigger an alarm (e.g.…”
Section: 10mentioning
confidence: 99%
“…Utilizing a pulsed laser with a gated ICCD detector offers the potential to make time-resolved measurements in addition to ambient measurements. 28 This approach can allow avoidance of fluorescence in luminescent minerals 35 or the creation of a combined Raman/laser-induced fluorescence (LIF) instrument that is capable of greater accuracy in the identification of an unknown sample. 3 Sharma has reported that a typical gate delay of 10 ns is needed to collect Raman without fluorescent interference in a Raman/LIF system.…”
Section: Instrumentationmentioning
confidence: 99%
“…27 Carter et al have reported standoff detection of high explosive materials at 50 meters in ambient light conditions using a small Raman instrument. 28 Sharma et al measured remote Raman spectra of minerals and organic compounds to 100 m. laser pulse at a distance of 213 m. 30 Using semi-portable equipment, Wu et al have reported on Raman spectroscopic identification of man-made organic compounds at distances of over half a kilometer. 31 A remote Raman system with Raman imaging capability has potential for determining mineral distribution and composition on a rock surface by comparing a set of Raman images collected for various minerals.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the effect of Raman scattering allows to detect and identify substances not only in the gaseous phase, but also in the liquid and solid phases. Solution of the problem of development of the lidar method for the remote detection and identification of traces of chemical compounds on the surfaces of various items is of great practical and scientific interest and should be studied to assess its sensitivity, noise-stability, and the application field [3][4][5]. For this purpose, the work was done to upgrade and use the Raman-lidar method for the detection of traces of high-energy nitrogen-containing chemical compounds on the surface.…”
Section: Introductionmentioning
confidence: 99%